2018
DOI: 10.1186/s13039-018-0393-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant chromosome 4 in two fetuses - case report and literature review

Abstract: BackgroundRecombinant chromosome 4 syndrome (rec 4 syndrome) is a rare genetic disorder, predominately resulting from a parental pericentric inversion of chromosome 4. To date, a total of 18 cases of rec (4) syndrome were published in literature. We report the first kindred of rec (4) syndrome analyzed using copy number variation sequencing (CNV-seq).ResultsA woman with two adverse fetal outcomes was described in the present study. The first fetus presented with severe intrauterine growth restriction, hyposarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the existing literature, more than 100 cases have been previously reported on 4q deletions [4,[8][9][10][11]. However, no cases had interstitial deletions sharing the same deleted segment as the present case.…”
Section: Methylsterol Monooxygenase 1 (Msmo1) [Mim 607545]mentioning
confidence: 47%
See 1 more Smart Citation
“…In the existing literature, more than 100 cases have been previously reported on 4q deletions [4,[8][9][10][11]. However, no cases had interstitial deletions sharing the same deleted segment as the present case.…”
Section: Methylsterol Monooxygenase 1 (Msmo1) [Mim 607545]mentioning
confidence: 47%
“…In 1967, Ockey et al first reported a deletion of the long arm of chromosome 4 in a child with limb abnormalities [7]. Since then, hundreds of patients with chromosome 4qsyndrome have been reported [4,[8][9][10][11]. The severity of the phenotype is correlated with the size of the deleted ranges (larger or smaller).…”
Section: Introductionmentioning
confidence: 99%
“…The present literature refers to several cases reporting 4q deletions, mostly terminal 4q deletion [1,[17][18][19][20]. There are also a few cases of interstitial deletions that have been reported.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recombinant chromosome 4 is a very rare chromosomal aberration with eighteen cases reported in the literature up to date [1][2][3][4][5][6][7][8][9][10][11]. All of the reported cases are due to parental pericentric inversion of chromosome 4.…”
Section: Introductionmentioning
confidence: 99%